Dietary salt supplementation: effects on fluid balance and exercise performance - Watson, P.; Pafili, Z.; Shirreffs, S. M. (The Journal of Physiology, 2002)
It has been suggested that hyperhydration prior to exercise may confer a performance benefit, through enhanced thermoregulation and altered metabolism (Luetkemeier & Thomas, 1994). Recently, salt (NaCl) supplementation of 120 mmol day-1 has been employed to increase plasma volume (PV) in patients suffering from orthostatic-related syncope (Mtinangi & Hainsworth, 1998). The aim of this study was to examine the effects of 6 days of dietary NaCl supplementation on fluid balance and subsequent exercise capacity in man. Five active males (mean ± S.D.; age 24 ± 1 years; mass 74.1 ± 6.0 kg; VO2,max 52.5 ± 3.6 ml kg-1 min-1) volunteered to participate in this ethics committee approved study. Initially subjects completed a VO2,max test and two familiarisation trials. Subjects entered the laboratory in the morning, following an overnight fast, on days 4 and 7 of each week over a 3 week period. Post-void nude body mass, resting blood pressure and whole body bioelectrical impedance were measured, and a venous blood sample was collected. An incremental cycle test to exhaustion was undertaken on day 7 of each week to assess exercise capacity. A 24 h urine collection was also made prior to each exercise test. In addition to their normal dietary intake standardised over the 3 week period, subjects received a 3 g day-1 placebo during weeks 1 and 3, or 5.844 g (100 mmol) NaCl day-1 during week 2. Supplements were administered in a single-blind manner, in the form of capsules and dissolved in flavoured water. Statistical significance (P < 0.05) between the experimental trials was evaluated using repeated measures one-way ANOVA, paired t test and Kruskal-Wallis tests as appropriate. Exercise capacity was not different following NaCl supplementation (12.46 ± 0.83 min; P > 0.05) compared with the placebo (Week 1 = 12.04 ± 0.87 min; Week 3 = 12.08 ± 0.87 min). No change in body mass was apparent during the study (P > 0.05), with fluid balance determined through calculated alterations to blood, cell and plasma volumes also found to be unaffected (all P > 0.05). The treatment resulted in no significant change to serum Na+ and K+ concentrations (P > 0.05), or to serum osmolality (P > 0.05). 24 h urinary Na+ was significantly elevated following supplementation (+104.8 mmol; P < 0.05), despite little observable change in K+ and Cl- excretion (P > 0.05). No difference in urinary flow rate was recorded during the experimental period (P > 0.05) These findings suggest that NaCl supplementation of 100 mmol day-1 did not increase total body water, expand PV or improve exercise capacity. It seems that fluid homeostasis may have been maintained through alterations in the release of hormones responsible for fluid regulation, leading to the excretion of the supplemented Na+.